2019
DOI: 10.1103/physrevd.100.044037
|View full text |Cite
|
Sign up to set email alerts
|

Scalar-metric-affine theories: Can we get ghost-free theories from symmetry?

Abstract: We reveal the existence of a certain hidden symmetry in general ghost-free scalar-tensor theories which can only be seen when generalizing the geometry of the spacetime from Riemannian. For this purpose, we study scalar-tensor theories in the metric-affine (Palatini) formalism of gravity, which we call scalar-metric-affine theories for short, where the metric and the connection are independent. We show that the projective symmetry, a local symmetry under a shift of the connection, can provide a ghost-free stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 74 publications
(69 reference statements)
3
62
0
Order By: Relevance
“…In the literature, more attention has been given to theories with torsion, but recently there has been a great deal of interest for MAGs with non-metricity, see e.g. [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, more attention has been given to theories with torsion, but recently there has been a great deal of interest for MAGs with non-metricity, see e.g. [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the scalar-tensor theories, it was recently found that an additional local symmetry of the connection is associated with the ghost-free structure when the spacetime geometry is extended from Riemannian one [35,36]. Similar considerations are certainly worthwhile in the context of higher curvature theories.…”
Section: Discussionmentioning
confidence: 86%
“…[57] and has recently gained increasing attention [58, (see also Refs. [82][83][84][85][86]). When the Higgs field relaxes to its electroweak vacuum after inflation, the usual Einstein-Hilbert gravity of GR is retained regardless of the choice of formalism, i.e.…”
Section: Decomposing the Actionmentioning
confidence: 99%